Modified asphalt production from the hydrocarbon resin, SBS and LDPE - Al-gharagholi, Safwat Jamal Ali Salih; Abdul-Hameed, Haydar Mohamad (Journal of Petroleum Research and Studies, 2020)
Modern highway transportation faces many challenges such as high traffic density, heavy load and high speed thus the asphalt pavements are founded to be subjected to various types of distress. That can be done by looking for good material to be added to the asphalt mix such as polymers LDPE, SBS and HR as shown by some researchers. The main objective of the work is to find new bitumen mix which is compatible with the Iraqi standard and saved the environment. The result indicates an improvement in most of the modified bitumen with HR, SBS and LDPE. 10% WCO, 88% bitumen and 2% HR give 60 mm Penetration, 99.3% solubility, 95 ductility, 44 oC softening point and 288 flash point were seen to be optimum with the selected standard. At the end, the study indicates that a good quality bitumen can be achieved using HR, SBS and LDPE.